2019
DOI: 10.1002/dvdy.110
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear gene expression‐phenotype relationships contribute to variation and clefting in the A/WySn mouse

Abstract: Background Cleft lip and palate is one of the most common human birth defects, but the underlying etiology is poorly understood. The A/WySn mouse is a spontaneously occurring model of multigenic clefting in which 20% to 30% of individuals develop an orofacial cleft. Recent work has shown altered methylation at a specific retrotransposon insertion downstream of the Wnt9b locus in clefting animals, which results in decreased Wnt9b expression. Results Using a newly developed protocol that allows us to measure mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…In A/WySn embryos with CL/P, the 5′ LTR of the clf1 IAP element is unmethylated [ 63 , 65 , 66 , 67 ] ( Figure 1 B, lower panel). 5′ LTR initiated antisense IAP transcripts and reduced Wnt9b levels are detected in CL/P A/WySn embryos compared to phenotypically normal A/WySn embryos, but the mechanism by which this occurs is unknown [ 63 , 67 ]. On a C57BL/6J (B6J) genetic background with the Clf2 modifier, the clf1 IAP element is more highly methylated, no IAP transcripts are detectable, and Wnt9b expression is normal [ 66 ].…”
Section: Evidence Of Strain-specific Erv Controlmentioning
confidence: 99%
“…In A/WySn embryos with CL/P, the 5′ LTR of the clf1 IAP element is unmethylated [ 63 , 65 , 66 , 67 ] ( Figure 1 B, lower panel). 5′ LTR initiated antisense IAP transcripts and reduced Wnt9b levels are detected in CL/P A/WySn embryos compared to phenotypically normal A/WySn embryos, but the mechanism by which this occurs is unknown [ 63 , 67 ]. On a C57BL/6J (B6J) genetic background with the Clf2 modifier, the clf1 IAP element is more highly methylated, no IAP transcripts are detectable, and Wnt9b expression is normal [ 66 ].…”
Section: Evidence Of Strain-specific Erv Controlmentioning
confidence: 99%
“…Despite a longstanding appreciation of the effects of canalization on phenotypic variation, the developmental mechanisms that underlie phenotypic robustness are less well understood. Several exciting recent studies have demonstrated how embedded properties of development, (processes inherent to trait development rather than mechanisms specific for canalization), can modulate phenotypic variation 5‐7 . Together, these studies indicate that nonlinearity in the genotype‐phenotype map may provide a general developmental mechanism for canalization.…”
Section: Introductionmentioning
confidence: 97%
“…Further experimentation could broaden the application of this protocol across mammalian and non‐mammalian species for which microCT studies are becoming more common. For example, this protocol could be combined with PaxGene fixation protocols to both preserve the ability for RNA extraction while improving contrast within soft tissue structures or potentially be applied to non‐mammalian species in which contrast‐enhanced microCT has been increasingly utilized to study development of soft tissue structures . Overall, the combination of detailed protocols for staining tissues with PTA and wax embedding to minimize tissue shrinkage and movement artifacts during scanning has broad applications.…”
Section: Resultsmentioning
confidence: 99%